Low-Dose Docetaxel/Cisplatin - Leucovorin and 46 Hour Infusional Fluorouracil in Metastatic Gastric Carcinoma - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2013)
Background: Phase II and III trials of docetaxel, cisplatin and fluorouracil (DCF) have shown superior efficacy versus cisplatin and fluorouracil alone but with high rates of hematologic toxicity in metastatic gastric cancer cases. To reduce toxicity while maintaining the efficacy of DCF, we investigated low dose docetaxel (D), cispatin (C) - leucovorin and fluorouracil (De Gramont regimen). Patient and methods: Chemotherapy-naive patients with metastatic gastric cancer (MGC) received D 60 mg/m(2) on day 1 and cisplatin 30 mg/m(2) on day 1-2 and the De Gramont regimen (Folinic acid 400 mg/m(2) on day 1 and 5-FU 2400 mg/m(2)/46h continuous infusion) every 3 weeks. The primary endpoint was response rate. Results: One hundred twenty patients with a median age of 52.5 years (range, 32-78) received a median of 6 cycles (range, 2-12 cycles). Of the 120 evaluable patients, 4 showed complete remission and 36 achieved a partial response. The overall response rate was 56.6%. Twenty eight patients (23.3%) showed stable disease and 52 (43.3%) progression. The median time to progression was 7 months (95% CI 6-7.9). The median overall survival was 15 months (95% CI 13.7-16.2). The most frequent hematological toxicity was leucopenia, which occurred at grade 3/4 intensity in 24 patients (20%). Conclusions: Low-dose DC-De Gramont regimen is active in MGC with a tolerable toxicity profile.
Keywords: Cisplatin; docetaxel; fluorouracil; gastric cancer; Turkey; SQUAMOUS-CELL CARCINOMA; LOCALLY ADVANCED HEAD; INDUCTION CHEMOTHERAPY; SUPPORTIVE CARE; PHASE-III; DOCETAXEL; CISPLATIN; CANCER; PLUS; TRIAL